Supramolecular Interactions In Aromatic Structures For Non-optical And Optical Chemosensors Of Explosive Chemicals - Juan Matmin; Nur Fatiha Ghazalli; Fazira Ilyana Abdul Razak; Hendrik O. Lintang; Mohamad Azani Abd Khadir Jalani (Trans Tech Publications Ltd., 2024)
Indexed by Scopus/ERA